Green Transformational Leadership in Enhancing Employees' Eco-Friendly Behavior Through Work Satisfaction at PT. Farm Surabaya - Naufal, Azel; Kusmaningtyas, Amiartuti; Mujanah, Siti (PT Inovasi Pratama Internasional, 2025)
This study aimed to examine the influence of green transformational leadership on employee green behavior, with job satisfaction as an intervening variable among employees in the hotel department of PT. Farm in Surabaya. The sample for this research consisted of 70 employees from PT. Farm in Surabaya. Data were collected using questionnaires, and data analysis was performed using path analysis with SmartPLS software. The results of this study indicate that green transformational leadership has a significant effect on employee green behavior, green transformational leadership has a significant effect on job satisfaction, and job satisfaction has an insignificant effect on employee green behavior. The variable proven to have a more dominant influence should be maintained at least and, if possible, enhanced